2023
DOI: 10.1128/spectrum.01287-23
|View full text |Cite
|
Sign up to set email alerts
|

Piscine Vitamin D Receptors Vdra/Vdrb in the Absence of Vitamin D Are Utilized by Grass Carp Reovirus for Promoting Viral Replication

Abstract: Grass carp reovirus (GCRV) is the causative agent of grass carp hemorrhagic disease, which seriously harms freshwater fish. Although many positive or negative regulators of GCRV infection have been identified in teleosts, little is known about the molecular mechanisms by which GCRV utilizes host factors to generate its infectious compartments beneficial for viral replication and infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Our previous study has shown that lowering cholesterol biosynthesis via lovastatin can block the production of VIBs mediated by grass carp vitamin D receptors Vdra/Vdrb ( 20 ). Since gcOSBP1 also promoted the numbers of VIBs, we next investigated the effect of cholesterol biosynthesis in the gcOSBP1-mediated promotion of GCRV replication.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous study has shown that lowering cholesterol biosynthesis via lovastatin can block the production of VIBs mediated by grass carp vitamin D receptors Vdra/Vdrb ( 20 ). Since gcOSBP1 also promoted the numbers of VIBs, we next investigated the effect of cholesterol biosynthesis in the gcOSBP1-mediated promotion of GCRV replication.…”
Section: Resultsmentioning
confidence: 99%
“…We previously have demonstrated that cholesterol and vitamin D receptors Vdra/Vdrb are vital for the generation of VIBs, which are important functional sites for viral replication ( 20 ). Grass carp ARF1, a member of the Ras superfamily, is recruited to VIBs, and co-localized with the viral nonstructural protein NS80 and NS38 of GCRV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations